Effectiveness and Safety of Ayurvedic Medicines in Type 2 Diabetes Mellitus Management: A Systematic Review and Meta-Analysis - Chattopadhyay, Kaushik; Wang, Haiquan; Kaur, Jaspreet; Nalbant, Gamze; Almaqhawi, Abdullah; Kundakci, Burak; Panniyammakal, Jeemon; Heinrich, Michael; Lewis, Sarah Anne; Greenfield, Sheila Margaret; Tandon, Nikhil; Biswas, Tuhin Kanti; et al. (Frontiers in Pharmacology, 2022)
Introduction: Many Ayurvedic medicines have the potential for managing type 2 diabetes mellitus (T2DM), with previous systematic reviews demonstrating effectiveness and safety for specific Ayurvedic medicines. However, many of the reviews need updating and none provide a comprehensive summary of all the Ayurvedic medicines evaluated for managing T2DM. Objective: The objective of this systematic review was to evaluate and synthesize evidence on the effectiveness and safety of Ayurvedic medicines for managing T2DM. Inclusion criteria: Published and unpublished RCTs assessing the effectiveness and safety of Ayurvedic medicines for managing T2DM in adults. Methods: The JBI systematic review methodology was followed. A comprehensive search of sources (including 18 electronic databases) from inception to 16 January 2021 was made. No language restrictions were applied. Data synthesis was conducted using narrative synthesis and random effects meta-analyses, where appropriate. Pooled results are reported as mean differences (MD) with 95% confidence intervals (CI). Results: Out of 32,519 records identified from the searches, 219 articles were included in the systematic review representing 199 RCTs (21,191 participants) of 98 Ayurvedic medicines. Overall, in the studies reviewed the methodology was not adequately reported, resulting in poorer methodological quality scoring. Glycated hemoglobin (HbA1c) was reduced using Aegle marmelos (MD -1.6%; 95% CI -3 to -0.3), Boswellia serrata (-0.5; -0.7 to -0.4), Gynostemma pentaphyllum (-1; -1.5 to -0.6), Momordica charantia (-0.3; -0.4 to -0.1), Nigella sativa (-0.4; -0.6 to -0.1), Plantago ovata (-0.9; -1.4 to -0.3), Tinospora cordifolia (-0.5; -0.6 to -0.5), Trigonella foenum-graecum (-0.6; -0.9 to -0.4), and Urtica dioica (-1.3; -2.4 to -0.2) compared to control. Similarly, fasting blood glucose (FBG) was reduced by 4 to 56 mg/dL for a range of Ayurvedic medicines. Very few studies assessed health-related quality of life (HRQoL). Adverse events were not reported in many studies, and if reported, these were mostly none to mild and predominately related to the gastrointestinal tract. Conclusions: The current evidence suggests the benefit of a range of Ayurvedic medicines in improving glycemic control in T2DM patients. Given the limitations of the available evidence and to strengthen the evidence base, high-quality RCTs should be conducted and reported.